Situational analysis of a social-ecological landscape in the Ahafo Ano Southwest District of Ghana - Atampugre, Gerald; Mensah, E.; Boateng, E.; Mabhaudhi, Tafadzwanashe; Cofie, Olufunke O. (CGIAR Initiative on West and Central African Food Systems Transformation, 2022)
A Social-Ecological Landscape (SEL) comprises a set of important resources (e.g., natural, socioeconomic, and cultural) whose flow and use are controlled by a mix of ecological and social subsystem dynamics. In developing countries, drivers of SEL changes are complex, and SEL pressures are growing. Areas endowed with natural resources (e.g., fertile soils, forests, water, minerals, etc.) tend to have high population growth rates and high poverty incidence. These tend to culminate in high demand for livelihood capitals (e.g., access to livelihood alternatives, education, food, health, water, forest resources, dwellings, roads, agriculture/aquaculture spaces, etc.). Further, multiple national and global stakeholders have continuedly to place a high demand on exploiting natural resources at the subnational.